2015
DOI: 10.2337/dc15-0658
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metformin on Metabolite Profiles and LDL Cholesterol in Patients With Type 2 Diabetes

Abstract: OBJECTIVEMetformin is used as a first-line oral treatment for type 2 diabetes (T2D). However, the underlying mechanism is not fully understood. Here, we aimed to comprehensively investigate the pleiotropic effects of metformin. RESEARCH DESIGN AND METHODSWe analyzed both metabolomic and genomic data of the population-based KORA cohort. To evaluate the effect of metformin treatment on metabolite concentrations, we quantified 131 metabolites in fasting serum samples and used multivariable linear regression model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
96
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 41 publications
4
96
1
4
Order By: Relevance
“…In fact, our analysis indicated that approximately 29% of the decrease in LDL-C can be explained by repressed FADS activity (2). Still, about 70% of the contribution to the reduction of LDL-C is unclear.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…In fact, our analysis indicated that approximately 29% of the decrease in LDL-C can be explained by repressed FADS activity (2). Still, about 70% of the contribution to the reduction of LDL-C is unclear.…”
mentioning
confidence: 70%
“…We thus wonder if the link between the studies can be drawn in such a straightforward manner. Additionally, the study by Giugliano et al (3) is based on the investigation of 12 obese hypertensive women without diabetes; therefore, the underlying design is different from ours (2).…”
mentioning
confidence: 87%
“…In the task of alluding to the mode of action of metformin, Xu et al (1) examined 131 fasting serum metabolites in three independent cross-sectional cohort studies. The authors found decreased concentrations of three metabolites (acyl-alkyl phosphatidylcholines [PCs]) in patients with type 2 diabetes treated with metformin compared with control groups not using glucose-lowering oral medication.…”
mentioning
confidence: 99%
“…Xu et al (1) are to be congratulated for their comprehensive study that brings substantial new knowledge to the enigmatic topic of metformin and its pleiotropic mode of action. However, in terms of LDL cholesterol reduction, we wish to draw attention to one mode of action that was not addressed in the study.…”
mentioning
confidence: 99%
“…[3][4][5] Recent research has shown that metformin significantly lowered blood levels of LDL-C by 11.83 mg/dL (P = 0.02) in patients with T2D. 6 Glueck et al 7 reported that in nondiabetic, morbidly obese subjects with body mass index greater than 30 kg/m2, metformin treatment for 29 weeks lowered LDL-C levels from 126 ± 34 mg/dL to 112 ± 43 mg/dL (P = 0.001), with a linear trend toward decreasing levels throughout (P = 0.036). It was believed that the effect of metformin was associated with adenosine 5-monophosphateactivated protein kinase (AMPK), AMPK activated by metformin can suppress fatty acid desaturases (FADS) synthesis in liver 6.…”
mentioning
confidence: 99%